Preparation and characterization of regenerated Bombyx mori silk fibroin fiber with high strength (eXPRESS Polymer Letters)
Regenerated Bombyx mori silk fibers were spun from hexafluoro-iso- propanol solution of silk fibroin sponge in methanol used as a coagulant solvent and then elongated in water. The stress-strain curves of the regenerated fibers changed dramatically depending on the draw ratio and the structure was studied by 13C CP/MAS NMR and X-ray diffraction methods. The patterns of 13C CP/MAS NMR spectra of two regenerated fibers with different draw ratios (1× and 3×) and native silk fiber are all β-sheet structure although the fraction of random coil/distorted β-turn decreases in the order of 1×, 3× and native fiber gradually. On the other hand, azimuthal scans of their X-ray fiber patterns changed remarkably with increasing the draw ratio. This indicates that long-range orientation of the fibroin chain changes remarkably during the drawing process, but the short-range local structure does not change significantly. Regenerated silk fiber with a draw ratio of 3× is a fiber with high strength which is comparable with that of natural silk fiber. The regenerated fiber is also more degradable than natural silk fiber in enzyme solution in vitro.